Comparison of cattle and sheep colonic permeabilities to horseradish peroxidase and hamster scrapie prion protein in vitro. Issue 6 (1st December 1999) - McKie, A T; Zammit, P S; Naftalin, R J
Abstract : BACKGROUND: Paracellular permeability to solutes across the descending colon is much higher in cattle than sheep. This is a possible route for transmission of infective materials, such as scrapie prion. AIMS: To compare the permeabilities of labelled scrapie prion protein and other macromolecules in bovine and ovine descending colons in vitro. METHODS: Using fresh slaughterhouse material, transepithelial fluxes of macromolecules across colonic mucosae mounted in Ussing chambers were measured by monitoring transport of either enzyme activity or radioactivity. RESULTS: The comparative bovine to ovine permeability ratio of the probes increased with molecular weight: from 3.1 (0.13) for PEG400 to 10.67 (0.20) (p<0.001) for PEG4000; and from 1.64 (0.17) for microperoxidase to 7.03 (0.20) (p<0.001) for horseradish peroxidase (HRP). The permeability of 125 I-labelled inactivated Syrian hamster scrapie prion protein (ShaPrP sc ) was 7.02 (0.33)-fold higher in bovine than ovine colon (p<0.0025). In each species, the probe permeabilities decreased according to the formula: P = Po .exp(−K.ra). The "ideal" permeabilities, Po are similar, however, K(ovine) = 2.46 (0.20) cm/h/nm exceeds K(bovine) = 0.85 (0.15) cm/h/nm (p<0.001) indicating that bovine colon has a higher proportion of wide pores than ovine. Image analysis confirmed that HRP permeated through the bovine mucosal layer via a pericryptal paracellular route much more rapidly than in sheep. CONCLUSIONS: These data may imply that scrapie prion is transmitted in vivo more easily across the low resistance bovine colonic barrier than in other species.